Fabrication and characterization of chitosan-based polymeric nanoparticles of Imatinib for colorectal cancer targeting application - Bhattacharya S. (My University, 2025)
The main objective of this research was to develop chitosan based polymeric nanoparticles of Imatinib (IMT-PNPs) for colorectal cancer targeting. The ionic gelation technique and central composite design was implemented to prepare IMT-PNPs. Out of 21 batches, F10 formulation was found to be optimized. The F10 was further evaluated for surface morphology, in-vitro drug release and release kinetic study, in-vitro drug deposition study, histopathological study, colon tissue uptake study using fluorescence microscopy, in-vitro cytotoxicity study & stability studies. The optimized formulations were found to have 208 ± 0.01 nm particle size, −32.56 ± 0.03 mV of zeta potential, 86.45 ± 0.05% in-vitro cumulative drug release & 68.52 ± 0.01% drug entrapment efficacy. Florescence study indicates epithelial colon cells parade higher fluorescent nanoparticle accumulation after i.v. administration. The IMT-PNPs formulations show only 0.46% hemolysis, which indicates the formulation is safer for i.v. administration. In histopathological evaluation, the final formulations show no sign of damage in tissues, which indicates the final formulation can be safely administered through i.v. route. From the MTT assay, it can be witnessed that encapsulated IMT-PNPs produces higher & controlled cytotoxicity in CT26 colon carcinoma cell lines. The outcomes of this research confined, IMT-PNPs could be an effective approach in colorectal cancer targeting using i.v. route. © 2020